Spinal epidural abscesses – The role for non-operative management: A systematic review. Issue 4 (August 2021) - Gardner, W.T.; Rehman, H.; Frost, A.
Abstract: Background: Spinal Epidural Abscesses (SEAs) are traditionally seen as a surgical emergency. However, SEAs can be discovered in entirely asymptomatic patients. This presents a dilemma for the attending clinician as to whether to subject these patients to significant surgery. This systematic review updates the evidence surrounding the efficacy of non-operative SEA management by means of intravenous antibiotics ± radiologically-guided aspiration. Aims: 1. To assess failure rates of medical therapy for SEA. The absolute definition of 'failure' used by the study was recorded, and comparisons made. 2. To review of risk factors for success/failure of medical treatment for SEA. Methods: A database search with the MESH term 'epidural abscess' and keywords ['treatment' OR 'management'] were used. Results: 14 studies were included. The number of SEA patients managed non-operatively ranged from 19 to 142. There was significant heterogeneity across the studies. Pooled Failure of Medical Therapy (FMT) (defined as any poor outcome) was 29.40%. When FMT = mortality the pooled rate was 11.49%. Commonly cited risk factors for FMT included acute neurological compromise, diabetes mellitus, increasing age and Staphylococcus aureus . Conclusion: SEA will always be a condition mostly managed surgically. Despite this, there is growing evidence that non-operative management can be possible in the correct patients. The key is in patient selection – patients with any of the above-mentioned risk factors have the potential to deteriorate further on medical treatment and have a worse outcome than if they had undergone emergency surgery straight away. Ongoing research will hopefully further investigate this crucial step.